School and peer influences on the academic outcomes of African American adolescents. (October 2015) - Butler-Barnes, Sheretta T.; Estrada-Martinez, Lorena; Colin, Rosa J.; Jones, Brittni D.
Abstract: Little scholarship explores how adolescents' beliefs about school and peers influence the academic outcomes of African American boys and girls. The sample included 612 African American boys ( N = 307, M age = 16.84) and girls ( N = 305, M age = 16.79). Latent class analysis (LCA) revealed unique patterns for African American boys and girls. Findings indicate that for African American boys, school attachment was protective, despite having peers who endorsed negative achievement values. Furthermore, socio-economic (SES) status was associated with higher grade point averages (GPA) for African American girls. Overall, these findings underscore the unique role of school, peer, and gendered experiences in lives of African American adolescents.